The chicken and egg story of a call centre in Malaysia - Alan, Chan Fun Foo; Tee, Keng Kok; Rathakrishnan, Thanuja; Ho, Jo Ann; Ng, Siew Imm (Emerald Publishing, 2021)
Learning outcomes: After attempting the case, users are able to: analyse issues and problems faced by a call centre in Malaysia. Determine the root causes of the problems faced by call centre employees and generate alternative solutions to solve the problems faced by the company and to ensure the sustainability of the business. Case overview/synopsis: This case was about the challenges faced by Daniel, the General Manager of an integrated security protection system company, Secure First (SF). Despite investing in the latest security technologies, conducting a major overhaul of the procedures, introducing an enhanced digital system at the call centre and providing training to the call agents, it was on the verge of losing its important long-term client due to its substandard performance. The client experienced major losses due to break-ins. After a thorough investigation, the problem surfaced in their call centre. Most of the staff were not familiar with the newly adopted system. The circumstances worsened when many of the call centre’s senior employees were tendering their resignations. The case discusses the aspect of employee satisfaction, staff performance that led to the turnover issue amongst employees in a call centre. The case explores what short-term and long-term strategies could Daniel suggest to change the call centre’s course to retain SF’s key account in times of desperation. Complexity academic level: This case has a moderate level of difficulty and may be used in undergraduate students. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 6: Human resource management.